Who Benefits from Training Courses in Germany? Monetary Returns to Non-formal Further Education on a Segmented Labour Market - Martin Ehlert (European Sociological Review, 2017)
While many advocate `lifelong learning' as the ideal career model, its impact on workers' lives is still partly unclear. Especially research on monetary returns to further education has yielded mixed evidence. I argue that a thorough assessment has to consider both the types of courses and the segmentation of labour markets. Using data from the German National Educational Panel Study, I test explanations of differing returns to non-formal further education in Germany, a country known for its highly segmented labour market. Results confirm that the returns to short non-formal training courses, which are the most common forms of further education in Germany, differ remarkably between types of courses and segments. Employer-mandated courses yield the highest returns, which is especially pronounced in internal labour markets. Furthermore, there are no returns on closed occupational labour markets. In occupations, where formal credentials are less important, returns to training are present. These results suggest that returns depend less on individual decisions to invest in training and more on the context. Hence, these findings go against human capital explanations and instead support implications of the Job Competition Model and Credentialism, which emphasize the importance of labour market structure.
Keywords: 330